A Study on the Causality Relationship between Total Capital Increase, Foreign Investments, and Tourism Sector Revenues in Azerbaijan - HUSEYNLI, Nigar (Journal of Environmental Management and Tourism, 2023)
The causation link between foreign investments in Azerbaijan, the country's overall capital expansion, and the growth of the tourist industry is examined in this paper. The Granger technique was used to ascertain the causal connection. The World Bank provided the data set needed for the analytical step. The findings of the research conducted to ascertain the connection between total capital rises, foreign investments, and tourist revenues in Azerbaijan demonstrate that there is some causation. The study's findings indicate that in Azerbaijan, economic development and tourist revenue are related. In other words, as the economy develops, the tourist industry in this nation expands and generates more revenue. In addition, it is evident that the growth of the tourist industry in this nation is successful in luring foreign capital to this nation. The growth of the tourist industry has a direct impact on the rise in total capital rises, just as it does on luring foreign investment into the nation. In other words, the growth of the tourist industry is the primary driver of both domestic and international investments. It is acknowledged that causation exists in each of the three situations.